Formation of intercultural-communicative competence: innovative project tasks - Zhusupova, Р.Ф.; Krassavina, Д.А.; Chouari, М. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2024)
The article focuses on implementing the use of innovative forms of project assignments in foreign language education to foster intercultural communicative competence among 9th-grade students. The study employed various methods, including literature review to define intercultural communicative competence and project assignments, surveys and tests with 9th-grade students, observation, and statistical analysis. The core of the article examines innovative approaches to developing intercultural communicative competence through project assignments related to foreign literature. These include tasks aimed at understanding cultural nuances, overcoming stereotypes and biases, and enhancing the ability to interact effectively with individuals from different cultures. Examples are provided of three-staged innovative project assignments focused on teaching the reading of short English stories. The study analyzed the benefits of using innovative project assignments in the context of English literature reading, such as fostering creative thinking, teamwork, communicative skills, and critical thinking. The conclusion summarizes the findings, emphasizing the significance of project assignments in foreign language education for developing students’ intercultural communicative competence.